Effects of apelin on reproductive functions: relationship with feeding behavior and energy metabolism - Tekin, Suat; Erden, Yavuz; Sandal, Suleyman; Onalan, Ebru Etem; Ozyalin, Fatma; Ozen, Hasan; Yilmaz, Bayram (Taylor & Francis Ltd, 2017)
Apelin is an adipose tissue derived peptidergic hormone. In this study, 40 male Sprague-Dawley rats were used (four groups; n=10). Apelin-13 at three different dosages (1, 5 and 50g/kg) was given intraperitoneally while the control group received vehicle the same route for a period of 14 days. In results, apelin-13 caused significant decreases in serum testosterone, luteinizing hormone and follicle-stimulating hormone levels (p<0.05). Administration of apelin-13 significantly increased body weights, food intake, serum low-density lipoprotein and total cholesterol levels (p<0.05), but caused significant decreases in high-density lipoprotein levels (p<0.05). Serum glucose and triglyceride levels were not significantly altered by apelin-13 administration. Significant decreases in both uncoupling protein (UCP)-1 levels in the white and brown adipose tissues and UCP-3 levels in the biceps muscle (p<0.05) were noted. The findings of the study suggest that apelin-13 may not only lead to obesity by increasing body weight but also cause infertility by suppressing reproductive hormones.
Keywords: Apelin; reproductive functions; food intake; body weight; uncoupling proteins